A Learning Development Based on Social Learning Networks Microsoft Teams in Animation Courses - Yulan Mardiati; Imbar Kunto; Cecep Kustandi (Jurnal Pembelajaran Inovatif, 2021)
This study aims to produce a product in the form of a Social Learning Networks (SLN) based learning design using the Microsoft Teams platform that can be used by students who are taking Animation courses at the Jakarta State University Technology Study Program. This research was conducted by following the ADDIE development model procedure, which consisted of 5 stages, namely (1) Analysis: conducting a needs analysis, students and materials, (2) Design: designing a learning design, (3) Development: developing a learning design, (4) ) Implementation: conducting trials on experts and users, (5) Evaluation: evaluating the results of product development based on the trials that have been done. Based on the trial results of the experts, the overall average value was 3.36 which means very good. While the results of the one to one and small group trials obtained an overall average of 3.55 which means very good. The results of this development research indicate that the learning design developed can be used to facilitate students in the learning process, especially online learning.